Ethnic and Gender Influences on Adaptive Behaviour of some Nigerian Children - Akinsola, Esther Foluke; Goma, Ruth Omafume (Advances in Social Sciences Research Journal, 2016)
In this manuscript we summarize the results of a pilot study carried out to field test a newly developed adaptive behaviour scale for children that is culturally sensitive and expected to be culturally appropriate for Nigerian children. In addition we attempted to determine whether adaptive behaviour skill competence increased with age and the roles played by ethnicity and gender in the acquisition and demonstration of adaptive behaviour skills. The children were sampled from the three Nigerian major ethnic groups namely Yoruba, Igbo, and Hausa who are resident in Lagos, Nigeria. 282 children aged 2-9 years were rated by their class teachers using the newly developed adaptive behaviour scale for children [3]. The results obtained from this study indicated that: (i) the development and demonstration of adaptive behaviour skill competence increased with age; (ii) at particular age group levels, ethnicity significantly and differentially increased adaptive behaviour skill competence in all the skill domains; (iii) in the communication domain and also at particular age group levels gender significantly and differentially increased adaptive behaviour skill competence of the children. There was no significant main effect for ethnicity and gender. The scale items were found to be culturally appropriate for Nigerian children. It was therefore concluded that further research is needed to establish an overall influence of ethnicity and gender on the acquisition and demonstration of adaptive behaviour skill competence in Nigerian children.